Strategy and Model of Socialization of Draft E-Government Law to Citizens (G2C) - Yunas Derta Luluardi (Musamus Journal of Public Administration, 2022)
The United Nations ranks e-government and e-participation in various countries to measure the success of democratization. The wave of global spatial participation demands a social response in building a responsive legal order. Socialization of the Draft Law with the Website was annulled as a strategy to open a mouthpiece for accountable and responsive public aspirations. Resistance in the community becomes unavoidable because there is an inappropriate gap between the drafting of the bill and the aspirations of the people. This paper has succeeded in revealing the process of absorbing the aspirations of the people in the socialization of the draft law. Then explore strategies and models of participatory socialization of the current e-Government to Citizens-based Draft Law in Indonesia using the Netnographic method accompanied by testing through the Nvivo application. The findings of the absorption of people's aspirations based on e-government have been running but are not effective. This is evidenced by the fact that there are still bills that have not absorbed the aspirations of using e-participation. These deficiencies were answered by redesigning the formulation of the PUU Simas and “My Participation” so that the harmonization and simplification of the bill could be integrated.